(untitled) (CIPEEX, 2022)
A VERY COMMON DISEASE THAT AFFECTS THOUSANDS OF PEOPLE AROUND THE WORLD AND, WHEN NOT TREATED CORRECTLY, CAN WORSEN AND LEAD TO DEATH IS VENOUS THROMBOEMBOLISM (VTE). PATIENTS AFFECTED BY VTE MAY BE LINKED TO OTHER CONCOMITANT PATHOLOGIES, INCLUDING NEOPLASIA. THEREFORE, BASED ON A MINI LITERATURE REVIEW, A CORRELATION WAS OBSERVED BETWEEN PATIENTS WITH OR THAT ALREADY HAD CANCER AND VENOUS THROMBOEMBOLISM (VTE). THE REVIEWED ARTICLES THAT SUPPORTED THIS SUMMARY ARE INTENDED TO SUPPORT OR RULE OUT THE EXISTENCE OF CORRELATION OR RISK FACTORS AND TREATMENTS BASED ON THIS RELATIONSHIP. IN THIS SENSE, THERE WAS CONSENSUS ON THE EXISTENCE OF A LINK BETWEEN CANCER AND A GREATER PROPENSITY FOR VTE AND SEVERAL FACTORS THAT LEAD TO THIS INVOLVEMENT, SUCH AS THE TYPE OF NEOPLASM, AGE GROUP, SEX, IN ADDITION TO VARIOUS SYMPTOMATIC MANIFESTATIONS. IN ADDITION, THE CORRELATION BETWEEN NEOPLASIA AND VENOUS THROMBOEMBOLISM HELPS TO ELUCIDATE KEY POINTS ON IMPROVING BOTH THE TREATMENT AND PROPHYLAXIS OF VTE.